2003
DOI: 10.1016/s0009-2614(03)00782-6
|View full text |Cite
|
Sign up to set email alerts
|

Missing conformers. Comparative study of conformational cooling in cyanoacetic acid and methyl cyanoacetate isolated in low temperature inert gas matrixes

Abstract: A comparative conformational study of two related systems, methyl cyanoacetate (MCA) and cyanoacetic acid (CAA), is presented. Ab initio calculations predicted that both systems have two nearly isoenergetic conformers separated by similar low energy barriers (about 3 kJ mol À1 ). In xenon matrixes deposited at temperatures above 40 K for MCA and above 20 K for CAA only one conformer was observed for each of the two systems. However, below those temperatures two MCA and two CAA conformers were trapped into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
134
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(145 citation statements)
references
References 18 publications
11
134
0
Order By: Relevance
“…It also depends on the matrix material and increases for the series Ar, Kr, Xe. 22 In addition to spontaneous interconversion, transitions between conformers in matrix are known to be induced by infrared radiation, 19,23 such as from a Fourier transform infrared spectrometer. This is of much less concern in He droplets due to short time of flight during which the embedded molecules are only exposed to a single laser pulse.…”
Section: ͑4͒mentioning
confidence: 99%
“…It also depends on the matrix material and increases for the series Ar, Kr, Xe. 22 In addition to spontaneous interconversion, transitions between conformers in matrix are known to be induced by infrared radiation, 19,23 such as from a Fourier transform infrared spectrometer. This is of much less concern in He droplets due to short time of flight during which the embedded molecules are only exposed to a single laser pulse.…”
Section: ͑4͒mentioning
confidence: 99%
“…However, if thermally activated, this relaxation may occur over the barrier. 15 Indeed, the TtfCc transformation was induced by annealing of the sample to a temperature of 28 K! The rearrangement of the argon atoms in this thermal back conversion process should be nonsignificant, since the changes of the baseline in the experimental spectra observed upon annealing were negligible.…”
mentioning
confidence: 99%
“…Obviously, water impurities have longer relaxation times and longer diffusion paths on the Kr surface than with Ar. It is interesting to note in this connection the result of Reva et al [27] who demonstrated depletion of the low-barrier (~0.7 kcal/mole) cyanoacetic acid gauche conformers in the sequence of matrices Xe, Kr, Ar. It can be therefore inferred that relaxation on the surface of matrices plays an important role in depopulation of the low-barrier conformers.…”
Section: Resultsmentioning
confidence: 80%
“…One can see that, by extrapolations the reported experimental data [7,27], the conformers with barriers of about 0.7 kcal/mole can be easily conserved in the isolated state at 6 K. But it is possible only if the energy relaxation is very fast, otherwise, the population of conformers will change. Among the above-mentioned methods (HENDI, CRDS, and matrix isolation), the process of cooling is the longest in CRDS, which used seeded molecular beams, since gas-dynamic cooling occurs due to numerous collisions in the supersonic part of nozzle [29].…”
Section: Ftir Spectra and Conformations Of 2¢-deoxyuridine In Kr Matrmentioning
confidence: 81%
See 1 more Smart Citation